2004
DOI: 10.1111/j.1472-765x.2004.01578.x
|View full text |Cite
|
Sign up to set email alerts
|

Barotolerance is inducible by preincubation under hydrostatic pressure, cold-, osmotic- and acid-stress conditions in Lactobacillus sanfranciscensis DSM 20451T

Abstract: Aims: This study addresses the inducibility of barotolerance by preincubation of Lactobacillus sanfranciscensis DSM 20451 T under various sublethal stress conditions. Methods and Results: Stress conditions which reduce the growth rate of L. sanfranciscensis DSM 20451T to 10% of its maximum were determined. These conditions were met at 43, 12AE5°C, a pH value of 3AE7, 1AE9% NaCl, or 80 MPa respectively. In contrast to heat preincubation, other prestresses, including salt, cold and pressure led to an increase of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(31 citation statements)
references
References 41 publications
1
29
1
Order By: Relevance
“…It has been demonstrated that bacterial survival is greatly increased by the preceding induction of a stress response (Yousef & Courtney, 2003) and cross-protection among different stresses has been reported, e.g. acquisition of barotolerance by application of NaCl, low pH and low temperature (Scheyhing, Hormann, Ehrmann, & Vogel, 2004).…”
Section: Hhp Treatmentmentioning
confidence: 99%
“…It has been demonstrated that bacterial survival is greatly increased by the preceding induction of a stress response (Yousef & Courtney, 2003) and cross-protection among different stresses has been reported, e.g. acquisition of barotolerance by application of NaCl, low pH and low temperature (Scheyhing, Hormann, Ehrmann, & Vogel, 2004).…”
Section: Hhp Treatmentmentioning
confidence: 99%
“…In recent investigations, we have used lactic acid bacteria as Gram-positive model organisms applied to food biotechnology to study HHP-induced inactivation kinetics, mechanisms of stress response, and sublethal injury followed by cell death (16).…”
Section: Introductionmentioning
confidence: 99%
“…43,44) Piezotolerance is inducible in Lactococcus sanfranciscensis by preincubation under hydrostatic pressure, cold or osmotic shock, and acidity. 45) Spores of Bacillus species are germinated by a variety of stimuli including nutrients, some chemicals and mechanical treatments such as abrasion and high pressure. [46][47][48] Nutrients trigger the receptors GerA, GerB and GerK in the inner membrane of the spore, followed by release of the Ca 2þ -dipicolinic acid (DPA) depot and activation of enzymes CwlJ and SleB.…”
Section: Recent Advanced Studies Of the Effects Of High Pressurementioning
confidence: 99%